Modular synthesis of semiconducting graft co-polymers to achieve ‘clickable’ fluorescent nanoparticles with long circulation and specific cancer targeting - Creamer,A; Lo,Fiego A; Agliano,A; Prados,Martin L; Hogset,H; Najer,A; Richards,D; Wojciechowski,J; Foote,J; Kim,N; Monahan,A; Tang,J; et al. (Advanced Materials, 2024)
Semiconducting polymer nanoparticles (SPNs) are explored for applications in cancer theranostics because of their high absorption coefficients, photostability, and biocompatibility. However, SPNs are susceptible to aggregation and protein fouling in physiological conditions, which can be detrimental for in vivo applications. Here, a method for achieving colloidally stable and low-fouling SPNs is described by grafting poly(ethylene glycol) (PEG) onto the backbone of the fluorescent semiconducting polymer, poly(9,9′-dioctylfluorene-5-fluoro-2,1,3-benzothiadiazole), in a simple one-step substitution reaction, postpolymerization. Further, by utilizing azide-functionalized PEG, anti-human epidermal growth factor receptor 2 (HER2) antibodies, antibody fragments, or affibodies are site-specifically “clicked” onto the SPN surface, which allows the functionalized SPNs to specifically target HER2-positive cancer cells. In vivo, the PEGylated SPNs are found to have excellent circulation efficiencies in zebrafish embryos for up to seven days postinjection. SPNs functionalized with affibodies are then shown to be able to target HER2 expressing cancer cells in a zebrafish xenograft model. The covalent PEGylated SPN system described herein shows great potential for cancer theranostics.